Prevalence of cardiac amyloidosis among adult patients referred to tertiary centres with an initial diagnosis of hypertrophic cardiomyopathy. (1st February 2020) - Maurizi, Niccolò; Rella, Valeria; Fumagalli, Carlo; Salerno, Sabrina; Castelletti, Silvia; Dagradi, Federica; Torchio, Margherita; Marceca, Azzurra; Meda, Martino; Gasparini, Massimo; Boschi, Beatrice; Girolami, Francesca; et al.
Abstract: Background: Differential diagnosis of genetic causes of left ventricular hypertrophy (LVH) is crucial for disease-specific therapy. We aim to describe the prevalence of Cardiac Amyloidosis (CA) among patients ≥40 years with an initial diagnosis of HCM referred for second opinion to national cardiomyopathy centres. Methods: Consecutive patients aged ≥40 years referred with a tentative HCM diagnosis in the period 2014–2017 underwent clinical evaluation and genetic testing for HCM (including trans-thyretin-TTR). Patients with at least one red flag for CA underwent blood/urine tests, abdominal fat biopsy and/or bone-scintigraphy tracing and eventually ApoAI sequencing. Results: Out of 343 patients (age 60 ± 13 years), 251 (73%) carried a likely/pathogenic gene variant, including 12 (3.5%) in the CA-associated genes TTR ( n = 11) and ApoAI ( n = 1). Furthermore, 6 (2%) patients had a mutation in GLA. Among the remaining, mutation-negative patients, 26 with ≥1 CA red-flag were investigated further: 3 AL-CA and 17 wild-type-TTR-CA were identified. Ultimately, 32(9%) patients were diagnosed with CA. Prevalence of CA increased with age: 1/75 (1%) at age 40–49, 2/86 (2%) at age 50–59, 8/84 (9%) at age 60–69, 13/61 (21%) at age 70–79, 8/31 (26%) at age ≥80 (p for trend <0.01). Conclusions: Among patients referred with and initial diagnosis of HCM, CA was the most common unrecognized mimic (9% prevalence) and increased with age (from 1% at ages 40–49 years to 26% >80 years). Age at diagnosis should be considered one of the most relevant red flags for CA in patients with HCM phenotypes; however, there is no clear age cut-off mandating scintigraphy and other second level investigations in the absence of other features suggestive of CA. Highlights: Disease-modifying treatments for Cardiac Amyloidosis (CA) are mostly effective in the early disease stage. Implementation of appropriate screening efforts for CA diagnosis has become a clinical priority. Age-related screening strategies for CA should be considered in all patients presenting with an HCM phenotype after age 50. Among theseroutine genetic investigations for TTR should be considered in all patients. Such efforts may therefore improve yield of early diagnosis which is critical for effective treatment.